PERAN ORANG TUA PADA PROSES BELAJAR SISWA DI RUMAH SELAMA PANDEMI COVID-19 - Tri Puput Syariati; Sri Utaminingsih; Santoso (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The research aimed to: (1) describe the teachers' teaching patterns during the Covid-19 pandemic; (2) describe the students' learning patterns at home during the Covid-19 pandemic; (3) describe the role of parents in assisting students to study at home during the Covid-19 pandemic. This research was a type of field research. The respondents and subjects in this research were students and their parents from grade I to grade V at SDN Ngelowetan, Kecamatan Mijen, Kabupaten Demak. The instruments used in this research were interview guidelines and document checklists. The data were collected through observation, interviews, and documentation. The data were then analyzed using descriptive qualitative analysis, which included data collection, data reduction, data display, and conclusion drawing/verification. The results of the study revealed that: (1) teachers conducted online teaching through WhatsApp and YouTube applications. In WhatsApp, teachers formed a group for each class, while on YouTube, teachers created a YouTube channel containing learning videos; (2) students' learning patterns at home included guided learning patterns, auditory-visual learning patterns, and problem-solving learning patterns. These learning patterns were strategies used by students to solve problems given by the teacher; (3) the role of parents in accompanying students’ learning at home included supervising learning activities, supervising the use of learning time, and helping children overcome learning difficulties.